Analtyical structure of the multi-level model - 이성우 (서울대학교, 2004)
The purpose of the present study is to investigate the analytical structure of the multi-level model, which is also called to hierarchical model, random coefficient model etc. Although interests on the multi-level model are recently increasing in natural sciences as well as social sciences, the accurate understanding of the analytical structure of the model has never been dealt with. This analytical paper constructs five analytical questions and derives diverse ways to reach the answers for each question. The present study also argues that the multi-level model provides a powerful tool for analysis of the data within which the number of observations varies.
Keywords: Multi-level Model; Random Coefficient; Covariance Matrix; Heteroscedasticity; Multi-level Model; Random Coefficient; Covariance Matrix; Heteroscedasticity